2021
DOI: 10.1002/mrd.23460
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of RLIM inhibits XIST expression and improves developmental competence of cloned male pig embryos

Abstract: Ectopic expression of Xist on the putative active X chromosome is a primary cause of the low developmental efficiency of cloned mouse and pig embryos. Suppression of abnormal Xist expression via gene knockout or RNA interference (RNAi) can significantly enhance the developmental competence of cloned mouse and pig embryos. RLIM is a Xist expression activator, whereas REX1 is an Xist transcription inhibitor, as RLIM triggers Xist expression by mediating the proteasomal degradation of REX1 to induce imprinted and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…We previously demonstrated that the siRNA-mediated knockdown of RLIM, another XIST transcription activator, also suppressed XIST expression and improved the developmental rate of cloned pig embryos [ 16 ]. However, RNA interference of RLIM exhibited only a minor effect on increasing X-linked gene expression in the cloned pig embryos [ 16 ]. This was different from the result from knocking down YY1 in the cloned pig embryos.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously demonstrated that the siRNA-mediated knockdown of RLIM, another XIST transcription activator, also suppressed XIST expression and improved the developmental rate of cloned pig embryos [ 16 ]. However, RNA interference of RLIM exhibited only a minor effect on increasing X-linked gene expression in the cloned pig embryos [ 16 ]. This was different from the result from knocking down YY1 in the cloned pig embryos.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, cloning is a powerful tool that has wide applications in animal production, life science, and biomedicine. Nevertheless, the efficiency of SCNT embryos in developing to term is very low, at about 2% [ 14 , 15 ] in mice and 1% in pigs [ 16 ]. Such a low developmental rate of full-term SCNT embryos limits the application and development of the SCNT technique.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation